Real-time monitoring system for athlete based on blue-tooth wireless sensor network - Wang, P.; Wang, X. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
The thesis introduces a real-time monitoring system for athlete physical states and movement parameters based on Bluetooth wireless sensors network. The system is made up of athlete parameters acquisition terminal based on Bluetooth, wireless communication subsystem, athlete monitoring center. Athlete parameters acquisition subsystem acquires the main physical states and movement parameters continuously during training. The data is sent to athlete monitoring center with wireless communication. The monitoring center receives the data from each athlete and save it to database, and show on display as graph or numerical data. The change of physical states or movement parameters can be analyzed by computer to provide to trainer or athlete as an auxiliary means to improve performance.